NF-Protocadherin Regulates Retinal Ganglion Cell Axon Behaviour in the Developing Visual System. - Louis C Leung; William A Harris; Christine E Holt; Michael Piper (PLoS ONE)
Cell adhesion molecules play a central role in mediating axonal tract development within the nascent nervous system. NF-protocadherin (NFPC), a member of the non-clustered protocadherin family, has been shown to regulate retinal ganglion cell (RGC) axon and dendrite initiation, as well as influencing axonal navigation within the mid-optic tract. However, whether NFPC mediates RGC axonal behaviour at other positions within the optic pathway remains unclear. Here we report that NFPC plays an important role in RGC axonogenesis, but not in intraretinal guidance. Moreover, axons with reduced NFPC levels exhibit insensitivity to Netrin-1, an attractive guidance cue expressed at the optic nerve head. Netrin-1 induces rapid turnover of NFPC localized to RGC growth cones, suggesting that the regulation of NFPC protein levels may underlie Netrin-1-mediated entry of RGC axons into the optic nerve head. At the tectum, we further reveal a function for NFPC in controlling RGC axonal entry into the final target area. Collectively, our results expand our understanding of the role of NFPC in RGC guidance and illustrate that this adhesion molecule contributes to axon behaviour at multiple points in the optic pathway.